Ultrasonographic parameters of the liver, spleen and kidneys among a cohort of school children in Sri Lanka - Dianne Tania Dayanthi Warnakulasuriya; Pattiya Pathirennahalage Uddika Chamila Peries; Yaddehi Arachchillage Chaminda Rathnasekara; KaluArachchige Thushari Madurika Jayawardena; Angappulige Upasena; Anada Rajitha Wickremasinghe (BMC, 2017)
Abstract Background Liver, spleen and kidney dimensions on ultrasonography vary with the age, weight and ethnicity. Reference standards of these parameters for normal Sri Lankan children are not available. Our aim was to establish normative data for longitudinal length of liver, spleen and kidneys in healthy children. Method Three hundred fifty-seven children, 5-13 years of age were selected from two randomly selected schools in the Gampaha district in the western province of Sri Lanka. A questionnaire was administered to the parents after obtaining informed written consent. Participants were screened for risk factors for organomegaly and were examined by a trained officer. Children with a past history of infective, inflammatory, haematological, malignant, congestive, collagenous or congenital conditions that can affect the size of the organs were excluded as well as those with clinically evident malnutrition, anemia, lymphadenopathy or organomegaly. Ultrasonographic assessment was done using a high resolution real-time scanner with a 3.5 MHz convex transducer by a trained officer. Children with ultrasonographic abnormalities of organs were also excluded from the study and referred for further evaluation. Results The study comprised 332 children comprising 176 girls (53%). There was a significant difference in the longitudinal dimension of the liver between the two sexes with a higher value recorded among females (Mann Whitney U = 11,830.5, p = 0.037). Body weight was correlated with the dimensions of the liver, the spleen and the kidneys. On multiple regression analysis body weight significantly associated with all the organs. (p < 0.01) Percentile graphs for longitudinal length of liver, spleen, right and left kidneys were formed according to the body weight. Conclusion The organ dimensions showed the highest correlation with body weight. We hope the normal ultrasonographic values of healthy Sri Lankan children will assist in interpretation of sonographic examinations in daily clinical practice.